2020
DOI: 10.5194/acp-2020-1222
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How alkaline compounds control atmospheric aerosol acidity

Abstract: Abstract. The acidity of atmospheric aerosols regulates the particulate mass, composition and toxicity, and has important consequences for public health, ecosystems and climate. Despite these broad impacts, the global distribution and evolution of aerosol acidity are unknown. We used the particular, comprehensive atmospheric multiphase chemistry – climate model EMAC to investigate the main factors that control aerosol acidity, and uncovered remarkable variability and unexpected trends during the past 50 years … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, in the case of the forward and reverse reactions, they typically occur fast and thus the concentrations of the reactants and the products are generally assumed to be in equilibrium in the global model due to its relatively long timestep and large model grid. Note, however, that recent modeling studies showed that the metastable assumption applied here could lead to an increase of aerosols' acidity (i.e., regionally up to 2 pH-units in the presence of crustal elements over dust sources, and roughly 0.5 pH units globally; Karydis et al, 2020) compared to the stable aerosol state assumption (i.e., the aerosols both in solid and liquid phases).…”
Section: Thermodynamic Equilibrium and Atmospheric Acidity Calculationsmentioning
confidence: 68%
“…Nevertheless, in the case of the forward and reverse reactions, they typically occur fast and thus the concentrations of the reactants and the products are generally assumed to be in equilibrium in the global model due to its relatively long timestep and large model grid. Note, however, that recent modeling studies showed that the metastable assumption applied here could lead to an increase of aerosols' acidity (i.e., regionally up to 2 pH-units in the presence of crustal elements over dust sources, and roughly 0.5 pH units globally; Karydis et al, 2020) compared to the stable aerosol state assumption (i.e., the aerosols both in solid and liquid phases).…”
Section: Thermodynamic Equilibrium and Atmospheric Acidity Calculationsmentioning
confidence: 68%